Sistem Informasi Pendataan Peserta Lembaga Pelatihan Kerja (LPK) di Dinas Tenaga Kerja ,Kabupaten Asahan - Heri Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Information System for Participant Data Management in Vocational Training Institutions (LPK) is designed to enhance the efficiency and effectiveness of participant data management at the Department of Manpower in Asahan Regency. This system focuses on managing training participant data, encompassing registration, grouping, and reporting processes. The data management process includes recording participant identities, the type of training attended, training schedules, and evaluation results. The system is designed to streamline administrative workflows, minimize manual errors, and accelerate access to information. Participant data is recorded and stored automatically using a structured format, including details such as participant names, addresses, identification numbers, and training programs attended. This system is developed using web-based technologies, such as HTML and other supporting technologies, to ensure flexibility and ease of access for users. By implementing this system, it is expected that the data management of vocational training participants in LPKs can be conducted more efficiently, accurately, and integratively, thereby supporting the improvement of administrative service quality at the Department of Manpower in Asahan Regency. Keyword :Information System, Participant Data, Vocational Training Institution, Department of Manpower, Data Management.